The Oldest Georgian Hymn In "The Nine Martyred Children of Kola" - Ia Grigalashvili (The Kartvelologist - A Bilingual Peer-reviewed, Academic Journal of Georgian Studies, 2012)
The determination of the date of compilation of "The Nine Martyred Children of Kola" always gave birth to differences of opinions in Georgian scholarship. In the recent period the opinion that "The Nine Martyred Children of Kola" was written in the 2nd -3dr centuries is becoming popular. In support of this opinion I argue that dressing the children in white robes, their stepping down into the stream, singing of an improvised hymn by the priest might be characteristic of the church service practice of the 2nd -3 centuries. It is difficult ot define whether the hymn was translated from any language, or the author improvised it? It is clear that the translator must have based himself on the nature of the Georgian language, versification of that time, or hymn or form of a pagan hymn. The fact si that the hymn si of rhythmic character. I divided it into lines. As the author of "The Nine Martyred Children of Kola" notes, before baptism the children were not allowed to enter the church. Therefore the church ni the vilage of Kola had the form of acel and it didn't have a porch, the place for staying of catechumens. This must have taken place in the 2nd- 3rd centuries.